Gamifying the visit to places with valuable landscapes - Jesus, Rui (2020)
The landscape, in general, is full of meaning and has been studied over time by experts in diﬀerent ﬁelds. In 1992, the landscape was considered a World Heritage Site with the designation of "Cultural Landscape". Despite this relevance, in many regions, there are places with valuable landscapes that are unknown to most of the population. This paper describes a mobile tool for ﬁnding and sharing places with valuable landscapes, which includes gamiﬁcation components to motivate users to search for new places and share them. It is also presented an evaluation of the tool, in terms of user experience and including the assessment of gamiﬁcation features. The tests were carried out in the Cultural Landscape of Sintra, considered world heritage since 1995.